The role of calmodulin and calmodulin-dependent protein kinases in the pathogenesis of atherosclerosis - Mei-Fang Chen (Tzu-Chi Medical Journal, 2022)
Atherosclerosis is a chronic inflammatory disease that triggers severe thrombotic cardiovascular events, such as stroke and myocardial infarction. In atherosclerotic processes, both macrophages and vascular smooth muscle cells (VSMCs) are essential cell components in atheromata formation through proinflammatory cytokine secretion, defective efferocytosis, cell migration, and proliferation, primarily controlled by Ca2+-dependent signaling. Calmodulin (CaM), as a versatile Ca2+ sensor in diverse cell types, regulates a broad spectrum of Ca2+-dependent cell functions through the actions of downstream protein kinases. Thus, this review focuses on discussing how CaM and CaM-dependent kinases (CaMKs) regulate the functions of macrophages and VSMCs in atherosclerotic plaque development based on literature from open databases. A central theme in this review is a summary of the mechanisms and consequences underlying CaMK-mediated macrophage inflammation and apoptosis, which are the key processes in necrotic core formation in atherosclerosis. Another central theme is addressing the role of CaM and CaMK-dependent pathways in phenotypic modulation, migration, and proliferation of VSMCs in atherosclerotic progression. A complete understanding of CaM and CaMK-controlled individual processes involving macrophages and VSMCs in atherogenesis might provide helpful information for developing potential therapeutic targets and strategies.